Antioxidant Activity and Amino Acid Profile of "Dadih" from Various Regions in West Sumatra, Indonesia - Habibi, Nur Ahmad; Gusnedi, Gusnedi; Sartika, Wiwi; Ismanilda, Ismanilda (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Dadih or curd is a traditional product typical of West Sumatra which is made through natural fermentation using the lactobacillus plantarum bacteria in bamboo. Each region in West Sumatra makes curd in various ways that affect its quality. This study aims to determine the amino acid profile and antioxidant activity of curd from various regions in West Sumatra. The study was conducted by testing curd from 4 main curd center regions, namely Bukittinggi, Payakumbuh, Batusangkar and Alahan Panjang. Certain tests were applied to assess the protein content using the Kjedahl method, amino acids content using the HPLC method and antioxidant activity using the DPPH method. The test results showed that curd from Payakumbuh had a higher protein and amino acid content compared to other regions. Furthermore, such curd had the highest level of antioxidant activity towards free radicals compared to other regions, with an IC50 value of 95.11 ± 0.40 mg/kg, which was included in the strong category. There was a significant relationship between amino acid content and antioxidant activity of curd. It can be concluded that curd from Payakumbuh had the best amino acid content and antioxidant activity compared to other regions in West Sumatra.